Evaluation of seed germination and growth activity of plants of Dianthus awaricus Khar. in the conditions of inner mountain Dagestan - R. M. Osmanov; Z. A. Guseynova; A. N. Alibegova (Юг России: экология, развитие, 2022)
Aim. Study of the growth dynamics of Dianthus awaricus plants in field experimental conditions and of laboratory germination of seeds obtained in the introduction experiment.Material and Methods. Samples of D. awaricus seeds collected in natural populations along the altitudinal ecocline from 820 to 1,720 m above sea level served as the material for the study. To study the field germination and growth dynamics of the plants, D. awaricus seeds were sown at two experimental bases of the Mountain Botanical Garden (at 1,100 and 1,750 m above sea level). Evaluation of laboratory germination was carried out using seeds collected at the Tsudakhar base.Results. Comparative characteristics of the average values of the shoot length and the number of lateral branches of the studied samples showed that the differences between the populations are significant. The monthly increase in D. awaricus plants of different accessions also differs. Monthly variability of the shoot length of D. awaricus in the tested accessions is at a high level, the expressivity of which, apparently, is significantly affected by a complex of environmental factors. A study of the germination of D. awaricus seeds showed that it is higher under laboratory conditions than under experimental field conditions. The highest percentage of seed germination was observed in the “Gunib” sample: 64.0% in the laboratory and 28.6% in the field at the Tsudakhar base.Conclusions. Differences were noted in growth dynamics in the studied samples of D. awaricus studied, apparently due to a complex of abiotic and biotic environmental factors. For the “Tsudakhar” samples the experimental conditions and place of collection of seed material were identical but for the other two samples they were different from their natural habitat. The low field germination of D. awaricus seeds is probably due to the negative impact of winter drought and adverse weather conditions in the spring.